Melatonin and circadian rhythms in liver diseases: Functional roles and potential therapies. Issue 3 (4th March 2020) - Sato, Keisaku; Meng, Fanyin; Francis, Heather; Wu, Nan; Chen, Lixian; Kennedy, Lindsey; Zhou, Tianhao; Franchitto, Antonio; Onori, Paolo; Gaudio, Eugenio; Glaser, Shannon; Alpini, Gianfranco
Abstract: Circadian rhythms and clock gene expressions are regulated by the suprachiasmatic nucleus in the hypothalamus, and melatonin is produced in the pineal gland. Although the brain detects the light through retinas and regulates rhythms and melatonin secretion throughout the body, the liver has independent circadian rhythms and expressions as well as melatonin production. Previous studies indicate the association between circadian rhythms with various liver diseases, and disruption of rhythms or clock gene expression may promote liver steatosis, inflammation, or cancer development. It is well known that melatonin has strong antioxidant effects. Alcohol drinking or excess fatty acid accumulation produces reactive oxygen species and oxidative stress in the liver leading to liver injuries. Melatonin administration protects these oxidative stress‐induced liver damage and improves liver conditions. Recent studies have demonstrated that melatonin administration is not limited to antioxidant effects and it has various other effects contributing to the management of liver conditions. Accumulating evidence suggests that restoring circadian rhythms or expressions as well as melatonin supplementation may be promising therapeutic strategies for liver diseases. This review summarizes recent findings for the functional roles and therapeutic potentials of circadian rhythms and melatonin in liver diseases.